Managing Islamic Education Curriculum in Indonesian Schools: Best Practices and Policy Recommendations - Mustakim, Zaenal (Jurnal Penelitian, 2019)
Despite studies in the realm of Islamic education teaching has been extensively conducted, the application of Islamic education curriculum in Indonesian secondary schools receives scant academic attention from the previous researchers. To fill this void, the present exploratory case study aims to explain practices of Islamic education enacted as a nationally-mandated school subject in secondary schools and to explore to what extent the Indonesian government supports Islamic education teachers to handle this compulsory school subject. Four Islamic education teachers of junior secondary schools volunteered to participate in this research. Data were garnered through classroom observation and in-depth interviews. Framed in thematic analysis, this study reports that the syllabus, lesson plan, learning resources, classroom-based practices, and authentic assessment required thorough concern. In response to this, the government support was needed to promote the best practices, i.e. teacher professional development and provision of sufficient school facilities. To policy authorities in Indonesia, the study recommends facilitating Islamic education teachers with sustainable professional development and redesigning the government-prescribed textbooks to foster teacher creativity in their teaching and learning processes.